2021
DOI: 10.1021/acs.joc.1c00019
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Molecular Cages with Sucrose and Cyclotriveratrylene Units for the Selective Recognition of Choline and Acetylcholine

Abstract: The synthesis of four fluorescent diastereoisomeric molecular cages containing cyclotriveratrylene and sucrose moieties connected via the naphthalene linkers is reported. These diastereoisomers were found to be selective and efficient receptors for acetylcholine and choline. Compound P -5a has a better affinity for choline over acetylcholine, while cage M -5a exhibits a higher association constant for acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…The opposite selectivity seems to be associated with the complementarity of each guest, with the cavity size and shape of the chiral twisted ((P)-285 and (M)-285) and non twisted ((P)-284 and (M)-284) geometry of each diastereoisomer (Figure 99). 227 Alonso-Goḿez, Cid, and co-workers synthesized the two enantiomers of a helical prism-like cage (286a) to show 10fold chiroptical amplification compared to its isolated building blocks. Initial studies have revealed that the cage could encapsulate an Fc + molecule as determined by 1 H NMR and HR-ESIMS, but no encapsulation was observed for Fc (Figure The presence of methyl groups significantly enhanced binding affinities from, for example, 50 M −1 to 900 M −1 for 290 + in CD 2 Cl 2 .…”
Section: Capsules and Cagesmentioning
confidence: 91%
See 1 more Smart Citation
“…The opposite selectivity seems to be associated with the complementarity of each guest, with the cavity size and shape of the chiral twisted ((P)-285 and (M)-285) and non twisted ((P)-284 and (M)-284) geometry of each diastereoisomer (Figure 99). 227 Alonso-Goḿez, Cid, and co-workers synthesized the two enantiomers of a helical prism-like cage (286a) to show 10fold chiroptical amplification compared to its isolated building blocks. Initial studies have revealed that the cage could encapsulate an Fc + molecule as determined by 1 H NMR and HR-ESIMS, but no encapsulation was observed for Fc (Figure The presence of methyl groups significantly enhanced binding affinities from, for example, 50 M −1 to 900 M −1 for 290 + in CD 2 Cl 2 .…”
Section: Capsules and Cagesmentioning
confidence: 91%
“…Fluorescent diastereoisomeric molecular cages 284 and 285 containing cyclotriveratrylene and sucrose …”
Section: Cages and Containers Soluble In Organic Solvents And Their A...mentioning
confidence: 99%
“…14 Host-guest assembly based on the selective recognition and encapsulation between the macrocyclic host and guest ligands has been applied in the synthesis and preparation of AuNCs to realize sensing and catalysis purposes. [15][16][17][18] For example, a recent study presented cucurbit [n]uril-decorated AuNCs as novel photonic materials with fascinating luminescence properties, arousing the interest of researchers. 19 The cucurbit [7]uril (Q7) with better water solubility and optimal ability to brighten AuNCs (Table S1 †) was selected in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, diastereoisomeric fluorescent cages with sucrose were reported by Szyszka et al for the recognition of Ch and ACh in acetonitrile. 16 Despite the fact that one of these hosts is selective for ACh (K ACh /K Ch = 3.1), the selectivity of the most efficient receptor for Ch is modest (K ACh /K Ch = 1.7). Thus, although some hosts selective for ACh exist, those for Ch are very scarce, and selective imaging of ACh or Ch with a fluorescent supramolecular host remains very challenging, more particularly in aqueous medium.…”
mentioning
confidence: 99%
“…HC 4 was not able to discriminate between ACh and Ch in organic solvent, but HC 1 , 2 , and 3 , which all have a tripodal benzenic platform as the second C 3 -symmetrical unit, were found to be selective for ACh ( K ACh / K Ch = 4.1, 2.8, and 4.4, respectively). Very recently, diastereoisomeric fluorescent cages with sucrose were reported by Szyszka et al for the recognition of Ch and ACh in acetonitrile . Despite the fact that one of these hosts is selective for ACh ( K ACh / K Ch = 3.1), the selectivity of the most efficient receptor for Ch is modest ( K ACh / K Ch = 1.7).…”
mentioning
confidence: 99%